2017
DOI: 10.1177/0886260517716941
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance for Intimate Partner Violence: A Comparative Study of Chinese and American College Students

Abstract: Tolerance for intimate partner violence (IPV) is an important correlate of interpersonal violent behavior. Although a large amount of research on IPV has been conducted in the West and a growing amount of studies on IPV in Chinese societies has been observed in recent years, only a small number of studies have analyzed IPV-related attitudes from an international and comparative perspective. Drawing on survey data collected from 1,178 college students from two Chinese and two U.S. universities, this study empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 55 publications
3
44
2
1
Order By: Relevance
“…Both Chinese and Spanish participants presented little tolerance for IPVAW and defined most offensive conduct as IPVAW. Nevertheless, similar to the results of comparative studies conducted in China and the US (Li et al, 2017), Chinese participants were less aware of the existence of violence and situation of victims and considered violence behaviors less serious than Spanish participants. Such difference may be explained by more news report and related legal enforcement in Spain (Menéndez et al, 2013).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Both Chinese and Spanish participants presented little tolerance for IPVAW and defined most offensive conduct as IPVAW. Nevertheless, similar to the results of comparative studies conducted in China and the US (Li et al, 2017), Chinese participants were less aware of the existence of violence and situation of victims and considered violence behaviors less serious than Spanish participants. Such difference may be explained by more news report and related legal enforcement in Spain (Menéndez et al, 2013).…”
Section: Discussionsupporting
confidence: 71%
“…In addition to research on prevalence and risk factors of IPVAW (e.g., Breiding et al, 2014;Devries et al, 2013;Gracia & Herrero, 2006), researchers have also focused on IPVAW related public atti-tudes (e.g., Li et al, 2017;Lin et al, 2016;Nabors & Jasinski, 2009;Sun et al, 2012;Waltermaurer, 2012;Wu et al, 2013). Attitudes toward IPVAW have been demonstrated to play a crucial role in predicting perpetration of IPVAW, women decision making capacity, and how the community and legal enforcement respond to violence (e.g., Flood & Pease, 2006;Rodriguez et al, 2018).…”
Section: A R T I C L E I N F Omentioning
confidence: 99%
“…Although existing literature finds a positive correlation between gender inequitable or IPV-accepting attitudes and suicidal behaviors, few studies have explored whether these relationships differ for women and girls who have and have not experienced IPV [ 23 ]. Previous evidence suggests that IPV survivors who believe IPV is acceptable may exhibit differential behaviors than their IPV-intolerant counterparts—such as one study which finds IPV survivors who endorse IPV are less likely to seek GBV services [ 35 , 36 ]. Yet, more evidence is needed on how these interactions influence outcomes of well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Across the globe, male intimate partners continue to be responsible for the majority of violence perpetuated against women (Devries et al, 2013), despite numerous reforms and public awareness highlighting the global prevalence and impact of intimate partner violence (IPV; Chibber & Krishnan, 2011). The majority of studies on IPV have focused on the prevalence of IPV either as physical and/or sexual (Devries et al, 2013;García-Moreno, Jansen, Ellsberg, Heise, & Watts, 2005;Parish, Wang, Laumann, Pan, & Luo, 2004;Straus, 2004), its causes (Jewkes, 2002;Ringel & Bina, 2007;Uthman, Lawoko, & Moradi, 2009), best policy and prevention practices (Breiding, Chen, & Black, 2014;Edleson, 2000), and associated public attitudes (L. Li, Sun, & Button, 2020;Lin, Sun, Wu, & Liu, 2016;Sun et al, 2012;Waltermaurer, 2012;Wu, Button, Smolter, & Poteyeva, 2013). Although research has found that attitudes and perceptions of IPV are one of the crucial predictors of IPV (Straus, 2004;L.…”
Section: Introductionmentioning
confidence: 99%